Las TAC al servicio de la formación inicial de maestros en el área de Didáctica de la Lengua y la Literatura: herramientas, usos y problemática - Eva Álvarez Ramos (Universidad de Cádiz, 2017)
The fast rise of information technology and communication (ICT) has made available to teachers so many resources that in many cases, teachers have been overtaken by the maelstrom of information that is available. This fact, which is not trivial, has ended up leading to a sacrifice of the didactic for the technological. We are confronted with an emptiness of concepts that are adorned by the claim and the visibility of the digital, and it seems that it is forgotten that are the learning technologies knowledge (LTK) which must be at our service and not the other way around.